Gender Gap and Present Status of Working Women in Corporate Arena: An Overview of Bangladesh Perspective - Kamal, Darina Rifat; Sabrin, Amina (Asian Journal of Managerial Science, 2014)
The landmark of this study is to illustrate the discriminate position of women in corporate sector and tries to unearth some challenges that women usually face in this world. The result shows that women are considered as the secondary workforce in corporate world. In spite of women’s great contribution, they are still at low ranks and have to face many problems in their professional career. Gender-balance or women-friendly environment in corporate world is still a myth in our country. So the main objective of this study is to figure out the reason of the untenable position of women in this male dominant field and provide some suggestions to overcome the quandaries that may help to amplify women’s participation in corporate sector in near future. We expect that this article will help the policy makers, managements of corporate world to understand the challenges of women and encourage them to introduce new policies, rules and regulations for women empowerment in this promising world. It may also facilitate the researchers for future research in this disregarded issue.